PRESCRIPTION AUDIT AT A TERTIARY CARE HOSPITAL – A CROSS-SECTIONAL STUDY - Das, Pranab; Biswas, Nilanjan; Saha, Nivedita; Tigga, Rohit; Singha, Arunima; Gupta, Aritra (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The aim of this study was to analyze prescribing practices at Silchar Medical College and Hospital (SMCH) through a cross-sectional audit of 600 outpatient prescriptions, adhering to the National Health Mission Prescription Audit Guidelines 2021. Methods: The audit examined prescriptions of patients who visited the Outpatient department (OPD) of Department of General Medicine, Surgery, Orthopedics, Gynecology and Obstetrics, Pulmonary Medicine, Pediatrics, Dermatology, and Psychiatry. The audit evaluated key aspects such as the completeness of patient information, legibility of prescriptions, documentation of clinical details, and adherence to standard treatment guidelines (STG). Results: The prescription audit at SMCH revealed high compliance with essential criteria such as OPD registration and patient gender documentation. However, gaps were identified in areas such as allergy status documentation (0%), legible handwriting (75.7%), and follow-up advice (16.9%). In addition, adherence to STG was observed in 75% of prescriptions, with a concerning finding that there was a lack of facility’s Antibiotic Policy. Conclusion: The study underscores the importance of complete and accurate prescription documentation to ensure patient safety and effective treatment.